Physical performance difference in community dwelling older adults with successful ageing, usual ageing and mild cognitive impairment - Rajwinder Kaur Hardev Singh,; Devinder Kaur Ajit Singh,; Suzana Shahar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Physical performance in older adults is known to decline with ageing. However, there is limited information about physical performance difference among older adults with; successful (SA), usual ageing (UA) and mild cognitive impairment (MCI). The purpose of this study was to compare the differences in physical performance among older adults in these three categorised groups. This study is part of a larger scale population based longitudinal study on neuroprotective model for healthy longevity among older adults (LRGS TUA). Physical performance was assessed using hand grip (HGT; upper limb strength), 2 minutes step (2MST; endurance), sit to stand (STS; lower limb strength), sit and reach (SRT; lower body flexibility), timed up and go (TUG; mobility and balance), back scratch (BST; upper body flexibility) and gait speed (GS; walking speed) tests. Cognitive status was measured using Mini Mental Status Examination (MMSE) for global function, Digit Span for attention and working memory; Rey Auditory Verbal Learning Test (RAVLT) for verbal memory. Participants were categorised in three groups; SA, UA and MCI. SA group were those without diabetes, hypertension, chronic lung disease, cancer, heart diseases and stroke, had normal scores in MMSE (score of >22), optimum self-rated health and no functional limitations measured using Instrumental Activities of Daily Living questionnaire (IADL). Participants with MCI had subjective information of cognitive impairment from caretakers, minimum or low functional limitation, global function with ≤ 19 score on MMSE and 1 SD from below the normal mean of the group for Digit Span and RAVLT. Older adults with UA had minimal or no functional limitation and average scores of MMSE, Digit Span and RAVLT which were between the scores of SA and MCI group. Data was collected among 1291 participants in Phase three of LRGS TUA study. Data was analysed for differences among the three groups using one way ANOVA test. The results showed that majority of older adults was categorized as UA group (71.14%), followed by SA (15.19% ) and MCI (12.72%). Higher performance in physical performance measures except in SRT were demonstrated in SA group compared to MCI and UA groups. Post hoc Sheffe test showed that there was a significant difference (p < 0.05) in the SA and UA group for all tests except for HGT and SRT. MCI and UA groups were significantly different (p < 0.05) in STS, TUG and GST tests. The results suggested that UA and MCI groups had reduced physical performance in lower limb muscle strength, mobility, balance and walking speed compared SA group. Promoting optimum physical performance is important among older adults for successful ageing.